Handling Kargo Import Motogp dengan Penggunaan Dokumen Ata Carnet dan Dokumen Pemberitahuan Pabean Kawasan Ekonomi Khusus (PPKEK) di Kawasan Ekonomi Khusus (KEK) Mandalika Tahun 2024 - Lalu Muhammad Yunan S.R; Aditya Dewantari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
MotoGP is a world-class motorcycle racing event involving participation from various countries around the world. In its implementation, it is necessary to import spare parts, vehicles, team equipment, and other technical equipment to circuits around the world, including Mandalika, Indonesia. This temporary import status makes MotoGP logistics require important documents, such as ATA Carnet and Customs Notification of Special Economic Zones (PPKEK) so that the goods can enter the Customs Area without being subject to customs and excise. This research method uses a qualitative method with a descriptive approach because it aims to understand in depth the process of handling MotoGP import cargo, especially related to the use of ATA Carnet documents and Customs Notification of Special Economic Zones (PPKEK) in the Mandalika Special Economic Zone. The results of this study indicate that the use of customs documents, such as ATA Carnet and Special Economic Zone Customs Notification (PPKEK) is used depending on the needs of each user who wants the entry of MotoGP logistics into Indonesia to be exempted from customs and excise so that these two documents become important instruments in implementing the temporary import status scheme for MotoGP logistics so that it can facilitate the handling process at Zainuddin Abdul Madjid International Airport to distribution to the Mandalika Special Economic Zone (KEK). The conclusion of this study is that with the existence of two customs mechanisms, namely ATA Carnet and Special Economic Zone Customs Notification (PPKEK), as well as the role of PT. Angkasa Pura Logistik in handling the flow of goods at the airport, the smoothness of MotoGP logistics is more guaranteed.